Association of cirrhosis of liver with gall-stone disease - Matin, ABMA; Rahman, ANMZa; Hossain, MZ; Hakim, HAN; Rahman, A (Journal of Dhaka Medical College, 2012)
DOI: http://dx.doi.org/10.3329/jdmc.v20i2.10532 J. Dhaka Med. Coll. 2011; 20(2): 116-118